2002
DOI: 10.1080/02652030110102836
|View full text |Cite
|
Sign up to set email alerts
|

Sulphonamide residues in eggs following drug administration via the drinking water

Abstract: The aim was to determine concentrations of sulphadimidine (SDM) and sulphadimethoxine (SDT) in eggs following oral administration through drinking water for 5 days (0.5 g l(-1) for SDT, 1 and 2 g l(-1) for SDM). Residues of sulphonamides in albumen and yolk were monitored by high-performance liquid chromatography with UV detection. The limit of quantification was 0.005 microg g(-1) for the two egg components. The results indicate that 0.9-1.4% of the dose administered was deposited in eggs. Maximum concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
5

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 15 publications
1
13
0
5
Order By: Relevance
“…Antibiotics have been used as growth promoters in the member states of the EU but concerns about development of antibacterial resistance led to the withdrawal of these agents as growth promoters in the EU since January 1, 2006 (Castanon 2007). Some antimicrobial drugs, such as sulphonamides are used to treat coccidiosis (Roudaut and Garnier 2002;Sentepe and Eraslan 2010). In veterinary medicine, the sulphonamides are effective chemotherapeutics for bacterial or protozoal diseases (EMEA 1995;BCFI 2010).…”
Section: Introductionmentioning
confidence: 98%
“…Antibiotics have been used as growth promoters in the member states of the EU but concerns about development of antibacterial resistance led to the withdrawal of these agents as growth promoters in the EU since January 1, 2006 (Castanon 2007). Some antimicrobial drugs, such as sulphonamides are used to treat coccidiosis (Roudaut and Garnier 2002;Sentepe and Eraslan 2010). In veterinary medicine, the sulphonamides are effective chemotherapeutics for bacterial or protozoal diseases (EMEA 1995;BCFI 2010).…”
Section: Introductionmentioning
confidence: 98%
“…Mean recovery was for albumen: SDD 87%, SDMX 77.4% and for Yolk: SDD: 64.6% and SDMX: 67.4%. UV detection at 275 nm yielded LOQ 0.005 mg/g (63).…”
Section: Sulfonamides In Foodstuffs Of Animal Origin 337mentioning
confidence: 99%
“…Different doses and routes of SDD residues have also been studied in laying hens (Blom 1975;Seib 1991;Furusawa 2001;Roudaut and Garnier 2002;Kan 2003). These studies indicated a transfer of sulfonamides into eggs, but mainly provided data on therapeutic doses.…”
Section: Introductionmentioning
confidence: 97%